PENGARUH PERSEPSI HARGA, KUALITAS PRODUK, DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN PADA KONSUMEN TOKO BANGUNAN KURNIA INDAH DI SIDOARJO - Abdul Malik Aziz; Yuliar Kartika W (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
The purpose of this study is to determine the effect of: 1). price perception on customer loyalty, 2). product quality on customer loyalty, 3). service quality on customer loyalty. This study used quantitative methods. The population in this study is consumers of Kurnia Indah Bungurasih Building Store. The sampling technique in this study used non-probability sampling. The sample used in this study was 90 respondents. Data analysis techniques use instrument tests, classical assumption tests, descriptive statistical tests, multiple linear regression tests, and hypothesis tests with the help of IBM SPSS Version 24 applications. The results of this study show that 1). Price perception has a significant effect on customer loyalty to consumers of Kurnia Indah Building Store in Bungurasih. 2). Product quality has a significant effect on customer loyalty at Kurnia Indah Building Store in Bungurasih. 3). Service quality has a significant effect on customer loyalty at Kurnia Indah Building Store in Bungurasih. Based on these findings, it is to increase loyalty Customers are advised to make efforts to improve the perception of price, quality and customer satisfaction.